Frequency and Significance of Ras, Tert Promoter, and Braf Mutations in Cytologically Indeterminate Thyroid Nodules: A Monocentric Case Series at a Tertiary-Level Endocrinology Unit - Simona Censi (Frontiers in Endocrinology, 2017)
PurposeThe management of thyroid nodules of indeterminate cytology is controversial. Our study aimed to establish the frequency and significance of H-,K-,N-RAS, TERT promoter, and BRAF gene mutations in thyroid nodes of indeterminate cytology and to assess their potential usefulness in clinical practice.MethodsH-,K-,N-RAS, TERT promoter and BRAF gene mutations were examined in a series of 199 consecutive nodes of indeterminate cytology referred for surgical excision.Results69/199 (35%) were malignant on histopathological review. RAS mutations were detected in 36/199 (18%), and 19/36 cases (53%) were malignant on histological diagnosis. TERT promoter mutations were detected in 7/199 (4%) nodules, which were all malignant lesions. BRAF mutations were detected in 15/199 (8%), and a BRAF K601E mutation was identified in 2 follicular adenomas and 1 noninvasive follicular thyroid neoplasm with papillary-like nuclear features. Altogether, this panel was able to identify 48% of the malignant lesions, achieving a specificity, positive predictive value, and negative predictive value for malignancy of 85, 62, and 75%, respectively.ConclusionThe residual malignancy risk in mutation-negative nodes is 25%. These nodes still need to be resected, but mutation analysis could help to orient the appropriate surgical strategy.